History of the Virginia Oyster Fishery, Chesapeake Bay, USA - Schulte, David M. (Frontiers in Marine Science, 2017)
Oyster populations in Virginia’s waters of Chesapeake Bay were lightly exploited until the early 1800s, when industrial fishery vessels first arrived, driven south from New England due to the collapse of northeastern oyster fisheries. Early signs of overexploitation and habitat degradation were evident by the 1850s. The public fishery, where oyster fishers harvest on state-owned bottom, rapidly developed after the Civil War and peaked in the early 1880s. Declines were noted by the late 1880s and prompted the creation of Virginia’s shell-planting and oyster-seed (young-of-the-year, YOY) moving repletion program in the 1920s. Despite management and increasing repletion efforts, the public fishery collapsed (annual landings < 10% of peak historical landings) by the early 1960s. The private leasehold fishery, in which individuals rent areas outside the public grounds to plant shells and oysters for their own private use, surpassed the public fishery by the late 1920s, partly masked this decline due to overfishing, habitat degradation and diseases until both public and private fisheries completely collapsed in the mid-1980s after a third disease outbreak. This disease outbreak was likely related to warming waters. Overfishing and concomitant habitat loss followed a pattern of sequential population collapses observed in wild oyster fisheries along the Coastlines of the United States and worldwide. In recent years, expanding hatchery-produced seed oysters and aquaculture significantly increased leasehold landings. The wild fishery has also increased as disease resistance developing naturally in the wild stocks, but remains approximately 5% of peak landings. Improved management has assisted in this recent limited recovery, improving these efforts further by enhancing stock recovery via large no-take sanctuaries, among other actions, could assist in stock recovery.